Particle Nucleation in the Initial Stage of Emulsifier‐Free, Emulsion Organotellurium‐Mediated Living Radical Polymerization (Emulsion TERP) of Styrene: Kinetic Approach. Issue 1 (2nd August 2016) - Kitayama, Yukiya; Yamashita, Nobuko; Okubo, Masayoshi
Abstract : Kinetic simulations of polymer chain propagation in an aqueous medium in an initial stage of emulsifier‐free, emulsion organotellurium‐mediated living radical polymerization of styrene with sodium poly(methacrylic acid)‐methyltellanyl as a control agent and 4, 4′‐azobis(4‐cyanovaleric acid) as a water‐soluble azo‐initiator at various polymerization temperatures, which is carried out experimentally at pH > 9 in a previous article, is performed using PREDICI software. Abstract : Kinetic simulations of polymer chain propagation in an aqueous medium in an initial stage of emulsifier‐free, emulsion organotellurium‐mediated living radical polymerization (emulsion TERP) of styrene with sodium poly(methacrylic acid)‐methyltellanyl (PMAA‐TeMe) as a control agent and 4, 4′‐azobis(4‐cyanovaleric acid) as a water‐soluble azo‐initiator at various polymerization temperatures, which is carried out experimentally at pH > 9 in a previous article, is performed using PREDICI software from CiTGmbH. The approach based on α ‐chain end‐separated kinetic simulation leads us to get important aspects of individual polymer chain growths from both α ‐end groups, i.e., initiator and PMAA end groups. The larger number percentage of polystyrene (PS) chain having PMAA end group relative to all PS chains is generated at lower polymerization temperature. In addition, the PS chain growth is also pronounced at lower temperature. In other words, the self‐assembly nucleation, in which the control agents are contained, predominantly occurs at the lower polymerization temperature than the homogeneous nucleation, in which they are not contained. This indicates that the emulsion TERP effectively proceeds at lower temperature, which is well accorded with the experimental result in the previous article.